Transcription factor TFIIE? interacts with two exposed positions in helix 2 of the Antennapedia homeodomain to control homeotic function in Drosophila. - Altamirano-Torres, C.; Salinas-Hernández, J.E.; Cárdenas-Chávez, D.L.; Rodríguez-Padilla, C.; Reséndez-Pérez, D. (PLoS ONE, 2018)
Homeoproteins contain the conserved homeodomain (HD) and have an important role determining embryo body plan during development. HDs increase their DNA-binding specificity by interacting with additional cofactors outlining a Hox interactome with a multiplicity of protein-protein interactions. In Drosophila, the first link of functional contact with a general transcription factor (GTF) was found between Antennapedia (Antp) and BIP2 (TFIID complex). Hox proteins also interact with other components of Pol II machinery such as the subunit Med19 from Mediator (MED) complex, TFIIE? and transcription-pausing factor M1BP. All these interactions clearly demonstrate Hox-driven transcriptional regulation, but the precise molecular mechanism remains unclear. In this paper, we focused on the Antp-TFIIE? protein-protein interface to establish the specific contacts as well as its functional role. Using Bimolecular Fluorescence Complementation (BiFC) in cell culture and in vivo we found that TFIIE? interacts with Antp through the HD independently of the YPWM motif and the direct physical interaction is at helix 2, specifically aminoacidic positions I32 and H36 of Antp. We also found, through ectopic assays, that these two positions in helix 2 are crucial for Antp homeotic function in head involution, and thoracic and antenna-to tarsus transformations. Interestingly, overexpression of Antp and TFIIE? in the antennal disc showed that this interaction is required for the antenna-to-tarsus transformation. In conclusion, interaction of Antp with TFIIE? is important for the functional specificity of Antennapedia, and amino acids 32 and 36 in Antp HD helix 2 are key for this interaction. Our results open the possibility to more broadly analyze Antp-TFIIE? interaction on the transcriptional control for the activation and/or repression of target genes in the Hox interactome during Drosophila development.